Personal Data Protection in the Blockchain Technologies - Sharafyan, N. (Bulletin of Yerevan University C: Jurisprudence, 2019)
In the frames of this paper, the author discusses the need for data protection in the new and innovative Blockchain technologies in the context of European and international new regulatory tendencies. The author tries to examine the possible discrepancies of existing legislation and technologies, as well as the legal issues on decentralized ledgers which are not yet covered. In addition, this article explains the concepts of “data controller” and “data processor” in Blockchain technologies, by identifying their roles and the boundaries of their responsibility. Finally, the author tries to discuss the applicability of the right to be forgotten in Blockchain technologies.